Design of Occupational Health and Safety Management Information System at Telogorejo Semarang Hospital - Hastuti, Dyah Dewi; Setyaningsih, Yuliani; Adi, Kusworo (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)))
Hospital is one of companies who has obligation to compose and develop SMK3 hospital. In the hospital SMK3 must do K3 recording and reporting integrity process with management information system of the hospital. The problems in the recording and reporting system are difficulty to access and search the data, not on time in input, difficulty in processing and analysis process data, often to lose the data and the result of the information is not complete. The purpose of this research is doing development management information system of K3 in Telogorejo Semarang Hospital and trial information system. The planning management information system of K3 in the hospital is formed by in method waterfall are problems and needs analysis, design system, implementation and trial to use blackbox method. This system who can be easier to take decision. The result from this research is formed of information system K3 in the hospital will be resulting output such as reporting and graph and system worked well and right in agreed hope and rules who has been explained by user system and be able to accomodate using multi-user. The conclusion of this research is the use of K3 RS information systems can facilitate input and process data, speed up data search, and produce more accurate output.